Kolaborasi Inovatif Mahasiswa dan SAMSAT dalam Meningkatkan Kesadaran Pajak Kendaraan Bermotor bagi Wajib Pajak Pemula di Kota dan Kabupaten Sukabumi - Aziz, Muh. Abdul; Amara Sofar, Diva; Trisilawati, Icha; Oktavianti, Morli; Ikbal, Muhamad; Rachmat Ali, Muhamad; Rival, Muhamad; Usep Hidayat, Mohamad (PT. Alahyan Publisher Sukabumi, 2025)
Tax awareness regarding motor vehicles among the community remains a challenge in supporting regional development. Students of Universitas Muhammadiyah Sukabumi, through the MBKM KKN program, collaborated with the SAMSAT offices of Sukabumi City and Regency to conduct outreach activities targeting senior high school (SMA/SMK) students as a strategy to enhance tax literacy and compliance from an early age. The activities were held at four secondary schools using interactive methods such as educational sessions, creative media, quizzes, and tax application demonstrations. The results showed an increase in students’ understanding of the importance of motor vehicle taxes and SAMSAT services. Partner evaluations also indicated positive student performance. This initiative demonstrates the importance of cross-sector collaboration in shaping a tax-aware generation.